KEWIRAUSAHAAN DALAM PENDIDIKAN AGAMA ISLAM - Nurdin, Nurdin; Muljawan, Asep; Stiarini, Matrdu (STAI Asy-Syukriyyah, 2025)
Entrepreneurship in Islamic religious education is a framework of thought and framework that regulates individual economic attitudes based on the principles and teachings of the Islamic religion. Islamic religious education emphasizes the importance of honesty, justice and transparency in all business transactions. This entrepreneurship prohibits practices such as riba (interest), gharar (uncertainty), and fraud. These values ​​aim to create a spirit of fair and balanced business, which does not only focus on worldly material gains but also on social and spiritual welfare. This study examines the main concepts of entrepreneurship in Islamic religious education, their implications for current and contemporary entrepreneurial practices, and how their implementation can improve justice and welfare in society. The results of this study are expected to provide insight for business actors in integrating the values ​​of Islamic religious education in entrepreneurial activities.